Composition of Synthesis Gas Produced by Intraformation Electrophysical Gasification of Coals at Different Heating Rates; Chemical and Petroleum Engineering; Vol. 53, iss. 3-4 - Larionov K. B. Kirill Borisovich; Yankovsky S. A. Stanislav Aleksandrovich; Tolokolnikov A. A. Anton Andreevich; Gubin V. E. Vladimir Evgenievich; Matveev A. S. Aleksandr Sergeevich (2017, 2017)
Title screen